Efeito do aumento da temperatura sobre a atividade colonial de abelhas sem ferrão na Caatinga (Melipona subnitida) - Silva, Antonio Gustavo Medeiros da (Universidade Federal Rural do Semi-Árido, 2017)
The Brazilian Tropical Dry Forest, the Caatinga, represents a challenging environment for bees owing to its extreme climatic conditions. Models of future climate scenarios point to an increase in ambient temperature by about 5°C until 2080 for this biome. Hence, studies are urgent that determine the possible impact of these climate changes on the native bee fauna. The present study aimed at identifying how colonies of Melipona subnitida, a study model for stingless bees (Apidae, Meliponini) of the Caatinga region, react to an increase in temperature. We posed the following hypotheses: (1) Colonies modify their foraging behaviour, reducing pollen collection and, as trade-off, increasing nectar collection with increasing temperatures. (2) The reduced pollen collection with increasing temperature results in a decrease in the number of constructed brood cells and in an increase in the number of destroyed brood cells. (3) Colonies collect more water with increasing temperatures. (4) Colonies prefer collecting more concentrated as well as less concentrated nectar (higher amplitude in sugar concentration of the harvested nectar) with increasing temperatures. The results of our study demonstrate that with increasing temperature the colonies (1) direct their foraging effort towards the collection of nectar, thus decreasing their pollen foraging effort; (2) reduce their brood cell construction; (3) collect more water; and (4) show an increasing amplitude concerning the sugar concentration of the collected nectar. The increasing foraging effort for nectar and water may be associated with the colonies' need for reducing the nest temperature in order to avoid overheating and the consequent death of individuals, particularly of the brood. The possible roles of the collected nectar in nest thermoregulation are (i) the supply of additional energy for ventilating bees (high sugar concentration preferred), and (ii) its use as liquid for evaporative cooling (low sugar concentration preferred owing to the elevated water content of the solution). However, reducing the pollen collection may result in a protein deficit for the colonies, which critically diminishes the production of new individuals. With this, the results of the present study reveal a potential problem for these bees in the face of the imminent climate changes predicted for the coming decades. Long before ambient temperatures reach critical or even lethal values for bees, the global warming may cause a reduction of the pollen foraging effort by the colonies. Consequently, the production of new bees will decrease, which, at long term, will lead to the collapse of the colonies
Effect of temperature increase on the colonial activity of stingless bees in Caatinga (Melipona subnitida)
Keywords: Aquecimento global; Abelha sem ferrão; Pólen; Néctar; Caatinga; Global warming; Stingless bees; Pollen; Nectar; Caatinga; CIENCIAS BIOLOGICAS::ECOLOGIA